To do or not to do? – Endometrial biopsy in younger women with abnormal uterine bleeding - Sandra Lynn Jaya-Bodestyne; Marlene Samantha Goh; Madeline Chan Hiu Gwan; Sonali Prashant Chonkar; Khurshid Merchant; Manisha Mathur (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Objective: Abnormal uterine bleeding (AUB) can be associated with underlying endometrial pathology. The current existing guidelines discuss the role of endometrial biopsy in women 40 years old and above, however, there are no clear recommendations for younger women. This study aims to identify the factors that increase the risk of endometrial pathology in women below 40 years of age presenting with AUB for consideration of endometrial biopsy. Methods: We conducted a retrospective observational study reviewing the records of 464 women aged under 40 years old who underwent endometrial biopsy for AUB. The data analysis included demographics, investigations undertaken, ultrasound findings, biopsy results, and treatment. Multivariable analysis was performed using modified Poisson regression models to compare women with endometrial hyperplasia (EH) (with or without atypia) and endometrial cancer (EC), to those with benign pathology, to identify risk factors for endometrial pathology. Results: In our study, 71.3 % of women had a benign histology, 22.8 % had EH with and without atypia and 2.2 % of women had a diagnosis of EC. A BMI ≥ 30 (RR 1.76, p = 0.002), nulliparity (RR 1.84, p = 0.001), ultrasound findings of thickened endometrium ≥ 15 mm (RR 1.39, p = 0.048) and cystic spaces in the endometrium (RR 1.83, p < 0.001) were identified as significant risk factors after a multivariate analysis. A combination of at least 3 of these risk factors had a cumulative increased risk of EH/EC (RR 3.80, p < 0.001). Conclusion: Endometrial biopsy in younger women with AUB should be carefully considered on a case-by-case basis and reserved for those with risk factors for a serious endometrial pathology.